Taxonomy and Molecular Phylogeny of Two New Urostylid Ciliates (Protozoa: Ciliophora) From Chinese Wetlands and Establishment of a New Genus - Song, Wenya; Zhang, Tengyue; Dong, Jingyi; Luo, Xiaotian; Bourland, William A.; Wang, Yurui (Frontiers in Microbiology, 2021)
Hypotrich ciliates with evolutionary novelties are constantly being discovered, challenging the current taxonomic system, and also attracting increased attention. In the present work, two new urostylid ciliates, Heterobakuella bergeri gen. nov., sp. nov. and Anteholosticha perezuzae sp. nov., collected from Chinese wetlands, were identified based on morphology and 18S rRNA gene sequences. Heterobakuella gen. nov. is defined by three frontal cirri, single buccal cirrus, one parabuccal cirrus, midventral complex composed of cirral pairs and one cirral row, one left and two right marginal rows, transverse and pretransverse cirri present, caudal and frontoterminal cirri absent. Heterobakuella can be easily distinguished from the morphologically most similar genus, Apobakuella, mainly by the single buccal cirrus (vs. one buccal cirral row) and one parabuccal cirrus (vs. several parabuccal cirral rows originated from different anlagen). Phylogenetic analyses show that H. bergeri branches within the clade formed by Bergeriella ovata, Monocoronella carnea, Anteholosticha gracilis, and Neourostylopsis spp., rather than the clade represented by Apobakuella. The other species, A. perezuzae, is mainly characterized by a distinctly slender body shape with an average length:width ratio about 7, distinctively-shaped biconcave, greenish cortical granules, and one or two pretransverse cirri. Phylogenetic analyses indicate the genus Anteholosticha is non-monophyletic.